Ringkasan kematangan emosional atlet sepak bola pria - Yanuarius Ricardus Natal; Yunita Victoria Natal; Andreas Johanis Lumba; Yohanes Bayo Ola Tapo (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2025)
Football players need emotional maturity to handle competitive pressure, teamwork, and decision-making. Emotional maturity can affect Citra Bakti Ngada football players' performance, team relationships, and responses to wins and losses. This research design uses a quantitative descriptive designand this study employs a quantitative descriptive method using a survey method. The subjects in this study are all male senior and junior football athletes at Citra Bakti Club, totalling 50 athletes aged 16 and 23 years, using a saturated sampling technique. The research instrument utilizes an emotional maturity scale adjusted to the context of football matches. Validity testing is conducted using Cronbach's alpha technique, while reliability testing is carried out using the product-moment formula with the assistance of SPSS. The results of this study indicate that the emotional maturity of Citra Bakti football athletes falls into three categories: low emotional maturity at 61.9% (14 athletes), moderate emotional maturity at 33.3% (24 athletes), and high emotional maturity at 4.8% (12 athletes). In conclusion, most football athletes at the Citra Bakti Ngada club have a moderate level of emotional maturity. Based on the research findings above, the researcher can offer several contributions to the management of professional football clubs as well as coaches from a psychological perspective, namely by adding variations of emotional regulation training that can be implemented in football clubs, such as relaxation techniques, deep breathing, or meditation, which can help athletes manage negative emotions and remain focused during matches.